The Influence of Service Quality, Price, and Convenience on Purchase Decisions of Gofood Services (Study on University of Muhammadiyah Gresik Students) - Fachri Ramadhan; Moh. Agung Surianto (Indonesian Vocational Research Journal, 2023)
This study aims to test the effect of service quality, price, and convenience on purchasing decisions for GoFood services. The method used in this study is a quantitative approach, through a questionnaire using a Likert scale. The population in this study were active students at Muhammadiyah University of Gresik. The sampling technique in this study used purposive sampling with a total sample of 100 respondents. The data collection technique used a questionnaire which was processed using SPSS version 25. The analytical model used in this study was a multiple linear regression analysis model. To find out the significance of the research variables partially on purchasing decisions, a t-test technique is used using a level of 5% or 0.05. The results show that service quality and convenience partially have a significant effect on purchasing decisions, and price partially has no significant effect on purchasing decisions.